Unveiling environmental transmission risks: comparative analysis of azole resistance in Aspergillus fumigatus clinical and environmental isolates from Yunnan, China - Jianchuan Gong; Jiarui Huang; Yongju Liu; Ying Zhang; Yuhong Gao (Microbiology Spectrum)
ABSTRACT Azole resistance in Aspergillus fumigatus poses a significant clinical challenge globally. Our previous epidemiological analysis revealed a remarkably high frequency (~80%) of azole-resistant A. fumigatus in Yunnan’s greenhouse environments, prompting increased local and regional research for targeted control strategies. In this study, we analyzed 94 clinical A. fumigatus isolates from Yunnan, comparing their susceptibility profiles and genotypic characteristics with environmental strains previously isolated. While the overall frequency of azole resistance in clinical isolates was lower than that in environmental samples, a significant prevalence of cross-resistance, with varying resistance patterns based on minimum inhibitory concentration (MIC) levels was observed, which exceeded rates in other regions of China. Specific mutation combinations in the cyp51A gene were linked to elevated MIC values in clinical and/or environmental samples, while some resistant strains with wild-type cyp51A remain unexplained, indicating a need for further investigation into their resistance mechanisms. The differences in unique genetic elements and the distinct genetic differentiation observed between clinical and environmental isolates can be attributed to Yunnan’s unique geomorphology and potential genotype importation from other provinces and abroad. Extensive allele exchanges and sharing contributed to the selection of azole-resistant clinical isolates, suggesting a common environmental origin, and the transmission routes of local drug-resistant strains cannot be excluded. These findings emphasize the imperative for regional and targeted surveillance to monitor resistance trends and guide effective antifungal therapy, and management strategies to mitigate invasive aspergillosis risk in this region.IMPORTANCEAzole resistance in Aspergillus fumigatus is a major global health concern, with particularly high rates (~80%) observed in Yunnan’s greenhouse environments. This study compares azole resistance in 94 clinical isolates from Yunnan with environmental strains, revealing lower clinical resistance but significant cross-resistance and distinct resistance patterns. Specific mutations in the cyp51A gene were associated with elevated minimum inhibitory concentration values, though some resistant strains had wild-type cyp51A, highlighting the need for further research. The unique genetic profiles and potential external genotype influences in Yunnan emphasize the need for targeted regional surveillance. Effective monitoring and control strategies are essential to manage and mitigate the risk of invasive aspergillosis.